Electrophoretic Coating based on Phenolic Resins - Wadhwani, Meena; Gupta, S.S. (Asian Journal of Chemistry, 2010)
Conventional organic coatings use a lot of organic solvents which are costly, scarce, toxic, pollutant and inflammable. Authors have developed oil-soluble phenolic dispersions in water thus avoiding organic solvents to a great extent. The colloidal dispersion of the resin can be coated on a metal surface by normal conventional methods or they can be electrocoated by making metal as anode.